Analisis Marjin Pemasaran Ubi Kayu (Manihot Utilissima) Di Kecamatan Polokarto Kabupaten Sukoharjo - Marleni, Yuni; Harinta, Yos Wahyu; Dewati, Rosita (Universitas Veteran Bangun Nusantara, 2023)
Cassava is the third food ingredient after rice and corn which is one of the leading agricultural products that is widely marketed in the Polokarto District area. The aim of this research is to determine the marketing channels, marketing margins and marketing efficiency of cassava that are most effectively used by cassava farmers in Polokarto District, Sukoharjo Regency. The basic method used in this research is descriptive which is aimed at highlighting facts, variables, circumstances and phenomena that are occurring now (when the research is taking place) and uses survey methods as a research technique. The results of this research are that there are 3 cassava marketing channels in Polokarto District, Sukoharjo Regency. In marketing channel I, the marketing institutions involved in cassava marketing are retailers. In channel II the marketing institutions involved are collecting traders, wholesalers and retailers. In channel III the marketing institutions involved are collecting traders and wholesalers. The marketing margin for marketing channel I is IDR 2,000, the margin for channel II is IDR. 13,450 and channel III margin is IDR 13,500. Farmer's share in channel I is 50%, channel II is 10.33% and channel III is 10%. The efficient marketing channel is marketing channel I with an efficiency level of 16.68%. Meanwhile, marketing channel II has an efficient level of 17.37% and marketing channel III has an efficient level of 28.07%. Based on this, it can be said that the most efficient is marketing channel I because it has the shortest channel so that the marketing costs that take place in this marketing channel pattern are the lowest and the farmer's share value is high in marketing channel I.